Religious, Moral and Political Influences on Abortion Support: Role of Financial, Emotional and Partner Justifications - Shahid, Saba; Brown, Mitch; Sacco, Donald F.; Stepanova, Elena V. (Studia Psychologica: Theoria et praxis, 2025)
We explored how various reasons for women to have abortions shape attitudes toward the procedure while similarly considering demographic variables predictive of one’s attitudes toward abortion. Participants (N = 302) read a single vignette presenting financial, emotional, or partner-related reasons for a hypothetical woman to have an abortion that varied in whether the reason was present for that woman. Participants completed measures assessing religiosity, conservatism, and moral foundations as candidate moderators for these effects. Despite the reason for abortions having no effect on attitudes themselves, various effects emerged implicating religiosity and conservatism as predictive of anti-abortion attitudes. Namely, more religious men were less supportive of the hypothetical woman’s abortion decision when driven by financial unreadiness, whereas more conservative men were less supportive of a target’s abortion decision when driven by emotional unreadiness and partner absence concerns. This study expands knowledge of factors contributing to abortion attitudes, thus informing public discourse on this divisive topic.